Synthesis of paracrystalline diamond - Tang, Hu; Yuan, Xiaohong; Cheng, Yong; Fei, Hongzhan; Liu, Fuyang; Liang, Tao; Zeng, Zhidan; Ishii, Takayuki; Wang, Ming-Sheng; Katsura, Tomoo; Sheng, Howard; Gou, Huiyang (Nature (London), 2021)
Solids in nature can be generally classified into crystalline and non-crystalline states 1 – 7 , depending on whether long-range lattice periodicity is present in the material. The differentiation of the two states, however, could face fundamental challenges if the degree of long-range order in crystals is significantly reduced. Here we report a paracrystalline state of diamond that is distinct from either crystalline or amorphous diamond 8 – 10 . The paracrystalline diamond reported in this work, consisting of sub-nanometre-sized paracrystallites that possess a well-defined crystalline medium-range order up to a few atomic shells 4 , 5 , 11 – 13 , was synthesized in high-pressure high-temperature conditions (for example, 30 GPa and 1,600 K) employing face-centred cubic C 60 as a precursor. The structural characteristics of the paracrystalline diamond were identified through a combination of X-ray diffraction, high-resolution transmission microscopy and advanced molecular dynamics simulation. The formation of paracrystalline diamond is a result of densely distributed nucleation sites developed in compressed C 60 as well as pronounced second-nearest-neighbour short-range order in amorphous diamond due to strong sp 3 bonding. The discovery of paracrystalline diamond adds an unusual diamond form to the enriched carbon family 14 – 16 , which exhibits distinguishing physical properties and can be furthered exploited to develop new materials. Furthermore, this work reveals the missing link in the length scale between amorphous and crystalline states across the structural landscape, having profound implications for recognizing complex structures arising from amorphous materials. A study describes the synthesis, structural characterization and formation mechanism of a paracrystalline state of diamond, adding an unusual form of diamond to the family of carbon-based materials.